(untitled) (CIPEEX, 2025)
The objective of this study is to analyze the impact of Artificial Intelligence (AI) on employment relationships, exploring how automation and digitalization are transforming the job market. It seeks to understand changes in skills demands, the sectors most affected by AI, and the challenges for workers and employers. Furthermore, the study aims to identify the opportunities and risks that AI poses to the economy and job vacancies. The methodology used consists of a review of academic literature and reports from global organizations, such as the International Labor Organization (ILO) and the World Economic Forum, which address the impact of AI on work. The research also includes case study analyzes of industries highly impacted by automation, such as manufacturing, transportation, financial services and customer service. The results indicate that AI is driving profound changes in employment relationships, especially in the way repetitive and manual tasks are being automated. Sectors such as manufacturing and transportation have seen a significant replacement of workers with AI systems such as robots and decision-making algorithms. At the same time, new job opportunities are emerging in technology-related areas, such as the development and maintenance of AI systems, data analysis and cybersecurity. This has generated a growing demand for workers with skills in programming, data science and machine learning. However, the study also points to growing inequality in the labor market. Workers with lower qualifications or in positions that involve easily automatable tasks are at risk of losing their jobs. On the other hand, those with advanced technical skills are better positioned to benefit from the opportunities created by AI. The research also revealed that the lack of requalification and continuous training programs exacerbates this inequality, especially in developing countries. Another important point is the transformation of work relationships. More flexible models, such as remote work and work via digital platforms, are expanding, impacting the way workers interact with companies and their employment contracts. AI is also being used in people management processes such as recruitment, performance evaluation and productivity control, which raises ethical questions about privacy and fair treatment in the workplace. The study concludes that AI is reshaping employment relationships in significant ways, both in terms of destroying jobs and creating new opportunities. The main challenge is to ensure that workers can adapt to this new reality through public policies that encourage requalification and the development of digital skills. AI also requires an overhaul of labor regulations to protect workers’ rights in increasingly digitalized and flexible environments. In short, while AI offers great potential to increase productivity and improve efficiency, it is essential that its adoption is accompanied by strategies that mitigate social